2000
DOI: 10.1677/joe.0.1650639
|View full text |Cite
|
Sign up to set email alerts
|

Improved glycaemic control in obese diabetic ob/ob mice using N-terminally modified gastric inhibitory polypeptide

Abstract: Gastric inhibitory polypeptide (GIP) is an important insulin-releasing hormone of the enteroinsular axis which is rapidly inactivated by the exopeptidase dipeptidyl peptidase (DPP) IV. The present study has examined the ability of Tyr 1 -glucitol GIP to be protected from plasma degradation and to enhance insulin-releasing and antihyperglycaemic activity in 20-to 25-week-old obese diabetic ob/ob mice. Degradation of GIP by incubation at 37 C with obese mouse plasma was clearly evident after 3 h (35% degraded). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 56 publications
(64 reference statements)
5
57
0
Order By: Relevance
“…Conversely, glucagon receptor antagonists may potentially be useful for the treatment of diabetes mellitus (Zhang and Moller, 2000;Petersen and Sullivan, 2001;Ling et al, 2002). Similarly, GIP analogs continue to be assessed for potential utility in the treatment of type 2 diabetes (O'Harte et al, 1999(O'Harte et al, , 2000, and disruption of the murine GIP receptor gene promotes resistance to weight gain and enhanced energy expenditure, suggesting that GIP receptor antagonism merits consideration for the treatment of obesity (Miyawaki et GLUCAGON RECEPTOR FAMILY al., 2002). Similarly, dipeptidyl peptidase-IV-resistant analogs of GLP-1 and GLP-2 are in clinical trials for the treatment of diabetes and intestinal disorders, respectively (Drucker, 1999a(Drucker, , 2001a(Drucker, ,b, 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, glucagon receptor antagonists may potentially be useful for the treatment of diabetes mellitus (Zhang and Moller, 2000;Petersen and Sullivan, 2001;Ling et al, 2002). Similarly, GIP analogs continue to be assessed for potential utility in the treatment of type 2 diabetes (O'Harte et al, 1999(O'Harte et al, , 2000, and disruption of the murine GIP receptor gene promotes resistance to weight gain and enhanced energy expenditure, suggesting that GIP receptor antagonism merits consideration for the treatment of obesity (Miyawaki et GLUCAGON RECEPTOR FAMILY al., 2002). Similarly, dipeptidyl peptidase-IV-resistant analogs of GLP-1 and GLP-2 are in clinical trials for the treatment of diabetes and intestinal disorders, respectively (Drucker, 1999a(Drucker, , 2001a(Drucker, ,b, 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NH 2 -terminal glucitol-GIP displayed markedly enhanced insulinotropic potency in clonal pancreatic -cells and improved in vivo biological activity in animals with type 2 diabetes (O'Harte et al 1998b(O'Harte et al , 2000. Based on these findings, and preliminary observations that substitution of the penultimate Ala 2 in GIP results in analogues with reduced DPP IV hydrolysis rates, we now report studies investigating the plasma stability, insulin-releasing activity and antihyperglycaemic properties of two novel NH 2 -terminal Ala …”
Section: Introductionmentioning
confidence: 85%
“…However, such structural modifications to the native GLP-1 molecule appear to impair receptor bindingactivation characteristics and insulinotropic activity, thereby compromising the benefits of protection from intrinsic DPP IV degradation. Recent studies in our laboratory have shown that an NH 2 -terminally glycated analogue of GIP (Tyr 1 -glucitol GIP) exhibits profound resistance to proteolytic DPP IV degradation, and displays enhanced cellular insulin-releasing and antihyperglycaemic activity in a commonly employed animal model of obesity-hyperinsulinaemic type 2 diabetes (O'Harte et al 1998b(O'Harte et al , 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…91 Non-specific glycosylation was found to improve metabolic stability and increase activity of gastric inhibitory proteins. [92][93][94] This strategy has been used to increase the half-life of erythropoietin, another glycoprotein, with at least one variant being approved by the Food and Drug Administration for the treatment of anemia. 95 The increased stability induced by glycosylation has made it a focus for peptide drug examination / development.…”
Section: Glycosylationmentioning
confidence: 99%